Surgical Management of Petroclival Meningiomas: Results and choice of an approach: https://doi.org/10.59156/revista.v37i02.496 - Abdala-Vargas , Nadin J.; Villalonga, Juan F.; Baldoncini, Matias; Campero, Alvaro (Revista Argentina de Neurocirugía, 2023)
Introduction: Meningiomas of the Petroclival Region (MRPC) are benign tumors that arise circumscribed in an anatomical region of difficult surgical access comprised, between the superior and middle clivus, and the posterior aspect of the petrous bone medial to the internal auditory canal. The surgical management of these tumors represents a challenge in modern neurosurgery. The object of the present work is describing the surgical results in a series of cases and to guide the reader in the selection of the appropriate surgical approach based on our experience. Materials and Methods: We included 30 patients operated on with MRPC from June 2005 to September 2022. Results: Of the 30 MRPC treated, the average age was 52.7 years, and the predominant sex was female in 83.3% of the cases. The most common implantation site was the petroclival fissure in 66% of cases. The most used surgical approach was the retrosigmoid in 44% of the cases followed by the presigmoid in 23%. A resection of 95% or more was achieved in 73% of the cases. Finally, we present nine relevant clinical cases. Conclusions: The results of this series coincide with the perception of the literature on the management of this pathology. The choice of an approach is a determining factor in achieving a promising surgical outcome.